Characteristics of effective nurse educators from Thai nursing students’ perspectives - Ausanee Wanchai; Chanakan Sangkhamkul; Benchamaphorn Nakamadee (Belitung Nursing Journal, 2022)
Background: Effective nurse educators will improve students’ performance. Therefore, examining the characteristics of an effective nurse educator is essential, especially from nursing students’ perspectives, which will provide an additional point of view to improve the teachers’ quality. Objectives: This research aimed to identify nursing students’ opinions regarding the characteristics of effective nurse educators and to compare those characteristics according to age, year of study, and cumulative grade point average. Methods: A descriptive quantitative design was used. Data were collected from 400 nursing students in Thailand using a validated questionnaire. Descriptive statistics, t-tests, and F-tests were used for data analysis. Results: The overall mean scores of effective nurse educators’ characteristics based on students’ perspectives were 4.36 (SD = 0.45). Subject expertise was the most essential characteristic of the effective nurse educators (Mean = 4.45, SD = 0.47), followed by relational expertise (Mean = 4.44, SD = 0.52), personality (Mean = 4.36, SD = 0.45), and teaching-related behavior (Mean = 4.33, SD = 0.46). The results also showed that participants with different cumulative grade point averages had no different views on the characteristics of effective nurse educators (p > 0.05). However, participants of different ages and years of study had significantly different perspectives on the characteristics of effective nurse educators (p < 0.05). Conclusion: The study offers necessary information regarding the essential characteristics of effective nurse educators. Therefore, nurse educators can use the study results to improve their desired characteristics. In addition, faculty development programs may be planned to help nurse educators improve these characteristics.